Risk profile of non-cicatricial alopecia in females - Khondker, Lubna; Nabila, Noshin; Hasan, M. Kamrul; Nath, Pankaj Kanti (International Journal of Research in Medical Sciences, 2025)
Background: Non cicatricial alopecia (NCA) is a common dermatological problem in female produces greater psychological distress. Understanding the risk factors and associations is essential for comprehensive assessments and effective management of various forms of hair loss. This study has been conducted with the aim to identify the possible risk profile of different types of NCA in female patients. Methods: A descriptive type of observational study was conducted to find out the risk profile of NCA in females. About 355 females with NCA attending the outpatient department of dermatology and venereology department, Bangladesh medical university, Bangladesh during study period were the study population. Data was collected through face-to-face interviews and clinical examinations along with laboratory investigations on all patients. Results: Among 355 female patients of NCA, age, duration of alopecia and family history of alopecia were significantly higher in patients with FPHL in comparison to patchy and diffuse pattern hair loss patients. Patients with diffuse alopecia had statistically significant association (p≤0.001) with CTD and history of taking OCP, oral steroid and hydroxychloroquine significantly more from the patients with other two patterns of NCA and the blood hemoglobin level was significantly lower in patients with diffuse alopecia. Conclusions: Diffuse alopecia was the most common type NCA, which was associated with connective tissue diseases (CTD); history of taking OCP, oral steroid and hydroxychloroquine and lower blood hemoglobin level. Age, duration of alopecia and family history of alopecia were significantly higher in patients with female pattern hair loss (FPHL) of NCA.